Endometriosis: A review of the diagnosis and pain management - Wei-W; Cynthia Chia Yng Kew; Bernard Su Min Chern (Wolters Kluwer Medknow Publications, 2015)
Endometriosis is characterized by the presence of endometrial tissues outside the uterus. It affects females in their reproductive years, and may be an estrogen-dependent condition. The estimated prevalence of endometriosis in the general population is as high as 10%, and is increased in females with subfertility. The diagnosis of endometriosis is usually suspected clinically and confirmed by transvaginal ultrasound or magnetic resonance imaging of the pelvis. The gold standard of diagnosis is surgical visual inspection of the pelvic organs by an experienced surgeon during laparoscopy. A positive histology will confirm the diagnosis; however, a negative histology does not exclude it. Serum cancer antigen-125 levels may be increased in women with endometriosis, however, it is a poor diagnostic tool in comparison to laparoscopy. The management of endometriosis is dependent on whether the primary problem is pain or subfertility. The primary objectives of an intervention include removing endometriotic implants, removing nodules or cysts, restoring normal anatomy, reducing disease progression, and providing symptomatic relief. Treatment must be individualized and take into consideration the impact of the condition on quality of life. This may require a multidisciplinary approach that involves a pain clinic and counseling services.